2013
DOI: 10.1002/mbo3.103
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity in the floral nectar of sevenEpipactis(Orchidaceae) species

Abstract: Floral nectar of animal-pollinated plants is commonly infested with microorganisms, yet little is known about the microorganisms inhabiting the floral nectar of orchids. In this study, we investigated microbial communities occurring in the floral nectar of seven Epipactis (Orchidaceae) species. Culturable bacteria and yeasts were isolated and identified by partially sequencing the small subunit (SSU) ribosomal RNA (rRNA) gene and the D1/D2 domains of the large subunit (LSU) rRNA gene, respectively. Using three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 61 publications
3
51
0
Order By: Relevance
“…Herrera, García & Perez 2008). Jacquemyn et al (2013) found high micro-organism diversity in orchid nectar in the same study area, especially in animal-pollinated species. Even though flowers where bagged 24 h prior to sampling to allow nectar accumulation; contamination of the nectar of flowers open prior to the bagging cannot be excluded.…”
Section: A R I a T I O N I N N E C T A R C O M P O S I T I O Nmentioning
confidence: 89%
“…Herrera, García & Perez 2008). Jacquemyn et al (2013) found high micro-organism diversity in orchid nectar in the same study area, especially in animal-pollinated species. Even though flowers where bagged 24 h prior to sampling to allow nectar accumulation; contamination of the nectar of flowers open prior to the bagging cannot be excluded.…”
Section: A R I a T I O N I N N E C T A R C O M P O S I T I O Nmentioning
confidence: 89%
“…Nectar-inhabiting microbes disperse across flowers via flower-visiting animals (Brysch-Herzberg 2004, Herrera et al 2010, Belisle et al 2012, Jacquemyn et al 2013, Schaeffer and Irwin 2014. Local communities of nectar microbes are highly ephemeral as the host flowers inevitably disappear as they wither, but the collection of flowers on a host plant functions as a microbial metacommunity that lasts longer than individual flowers while the plant is in bloom (Belisle et al 2012).…”
mentioning
confidence: 99%
“…Nectar is composed of various ratios of hexoses such as glucose, fructose, and sucrose with minor constituents such as amino acids, lipids, phenolic content, and esters [110, 111]. Nectar harbors a microbial community as well [112, 113]. Mosquitoes have a preference to certain plants as their energy source.…”
Section: Plant Derived Polyphenols and Microbiotamentioning
confidence: 99%